Anthropometric but not motor characteristics of young volleyball players were improved after a one-week-long intense training sports camp - Robert Podstawski; Joanna M. Bukowska; Krzysztof Borysławski; Elżbieta Biernat; Daria Grodź; Ferenc Ihasz; Jacek Wąsik (Scientific Reports)
Abstract This study aimed to examine potential changes in the anthropometric and motor characteristics of volleyball players aged 17.98 ± 0.51 years after participation in a week-long sports camp. Potential changes in anthropometric characteristics were determined by bioelectrical impedance, and the players’ motor characteristics were assessed in a reaction time test, grip strength test, 5 × 20 s interval test on a rowing ergometer, and vertical, approach and standing long jump tests. A decrease was observed in body fat mass (difference (Δ) of 1.0 kg, p = 0.015), percent body fat (Δ of 1.16%, p = 0.008), and the waist-to-hip ratio (Δ of 0.02, p = 0.001). An increase was noted in total body water (Δ of 1.0 L, p = 0.002), proteins (Δ of 0.33 kg, p = 0.001), minerals (Δ of 0.12 kg, p = 0.003), fat-free mass (Δ of 1.46 kg, p = 0.001), and skeletal muscle mass (Δ of 0.9 kg, p = 0.001). In the group of motor abilities, a significant increase was observed only in the grip strength of the left hand. In conclusion, week-long sport camps can significantly affect the body composition characteristics of young volleyball players, but they do not induce significant changes in motor abilities.